Thermal vision, moisture content, and vegetation in the context of off-road mobile robots. (April 2017) - González, Ramón; López, Alejandro; Iagnemma, Karl
Highlights: Impact that moisture content and vegetation produce on soil compaction. Field tests relating thermal properties to moisture content and vegetation. Field tests relating thermal properties to terrain traversability (loss of traction). Abstract: This paper describes an initial investigation that shows the major impact that moisture and vegetation produce on a soil and how that effect may be measured using a thermal camera. In particular, those two variables influence how the soil compacts and, hence, the traversability of a vehicle. A broad set of experiments, under different weather conditions and with different soils, demonstrate that thermal properties derived from the thermal camera (i.e. thermal inertia) increase when moisture content of sandy soils increases. In addition to that, a relation is observed between thermal inertia and traversability (lower thermal inertia, worse traction; and vice versa). Another key behavior is noticed for vegetated soils, where a similar thermal inertia to wet sand is obtained but with only a third of moisture content. These results may be considered for maximizing traversability over sandy soils with higher thermal inertias, what eventually means higher compaction and safer routes. To the authors' knowledge, this is the first work addressing the correlation between moisture content and vegetation, and the thermal properties of a soil using a light-weight thermal camera that can be mounted on a mobile robot.